Improving Employee Engagement of Muhammadiyah Teachers with Organizational Trust, Distributive Justice, and Psychological Empowerment - Cut Rifatmi Fadhilaini; Heru Kurnianto Tjahjono; Susanto Susanto (The Winners, 2021)
The research aimed to look at the factors that significantly influence the teacher’s engagement, especially the factors of organizational trust and distributive justice. In addition, the research was to see the moderating effect of psychological empowerment in the influence of organizational trust on employee involvement and between distributive justice on employee engagement using the hierarchical regression analysis method. The research implemented simple random sampling technique and obtained 150 respondents, who were teachers at Muhammadiyah schools spread across five schools in Kotagede District, Yogyakarta, Indonesia. The results show that organizational trust has a significant effect on employee engagement, while distributive justice does not significantly affect employee engagement. In addition to these factors, psychological empowerment is shown to have a quasi-moderating effect in the effect of organizational trust on employee engagement. Since the analysis is limited to only five Muhammadiyah schools in Kotagede, Yogyakarta, the results cannot generalized. In addition, the COVID-19 pandemic only makes the questionnaires possible via online. Since younger teachers start to dominate, future research is suggested to have a further analysis on different generations (X, Y, and Z).